UTILIZATION OF MARITIME WEATHER INFORMATION FOR SHIPPING SAFETY IN ACEH - Syindi Airikvita; Muliadi Sembiring; Thaib Rizwan; Ichsan Setiawan; Syarifah Meurah Yuni (CV. Naskah Aceh, 2026)
This community service project is entitled